A New Type of Capping Agent in Nanoscience: Metal Cations. Issue 18 (4th April 2019) - Liu, Jiawei; Wang, Shaoyan; Cai, Kai; Li, Yefei; Liu, Zhipan; Liu, Lingmei; Han, Yu; Wang, Hong; Han, Heyou; Chen, Hongyu
Abstract: Capping agents are the essential factor in nanoscience and nanotechnology. However, the types of capping agents are greatly limited. Defying conventional beliefs, here is shown that metal cations can also be considered as capping agents for oxide nanoparticles, particularly in maintaining their colloidal stability and controlling their facets. Here the general stabilizing effects of multivalent cations for oxide nanoparticles, and the facet controlling role of Al 3+ ions in the growth and ripening of Cu2 O octahedra, are demonstrated. This discovery broadens the view of capping agent and opens doors for nanosynthesis, surface treatment, and beyond. Abstract : Metal cations are considered as capping agents in nanoscience. Here, the general affinity of multivalent cations to oxide nanoparticles is reported, which leads to the increase of positive surface charge and colloidal stability. More importantly, Al 3+ ions can stabilize Cu2 O (111) facets better than the normal (100) facets, yielding Cu2 O octahedra instead of the normal cubes.